PENGUATAN LAYANAN PENDIDIKAN INKLUSIF MELALUI PEMETAAN PROFIL DAN KEBUTUHAN BELAJAR PESERTA DIDIK BERKEBUTUHAN KHUSUS - Idhartono, Amelia Rizky; Rafikayati, Ana; Hidayati, Nurul (Kanigara, 2026)
The implementation of inclusive education in schools still faces various obstacles, especially in identifying and mapping the profiles and learning needs of students with special needs accurately. Limited data and teachers' understanding of student characteristics often result in learning services, curriculum adaptation, and the provision of learning support not being in accordance with individual needs. In fact, mapping learning profiles and needs is an important step in realizing accessible, adaptive, and student-centered education services. Therefore, the Special Education Study Program of PGRI Adi Buana University Surabaya in collaboration with the East Java Provincial Education Office held a community service activity with the theme "Strengthening Inclusive Education Services through Mapping the Profiles and Learning Needs of Students with Special Needs" to increase the capacity of schools in providing more targeted and quality education services. Participants in this activity were 30 principals and teachers of SLB, SMA, SMK who provide inclusive education from various areas in Sampang Regency. The material presented in this activity includes: (1). Basic Concepts, Components, Instrument Structure, and Data Sources for Mapping the Profiles and Learning Needs of Students with Special Needs; (2). Practice and Assistance in Compiling Profile Mapping and Learning Needs of Students with Special Needs; (3). Assistance in Compiling Recommendations for Educational Services for Students with Special Needs.